Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1155/2020/4594630
|View full text |Cite
|
Sign up to set email alerts
|

Thymic Stromal Lymphopoietin Is Implicated in the Pathogenesis of Bullous Pemphigoid by Dendritic Cells

Abstract: Objectives. Both thymic stromal lymphopoietin (TSLP) and dendritic cells (DCs) are involved in many autoimmune diseases, but the potential roles of TSLP and DCs in bullous pemphigoid (BP) have not been clarified. We sought to explore the contributions of TSLP and DCs in patients with BP. Methods. TSLP levels in sera and blister fluids were measured by enzyme-linked immunosorbent assay. The TSLP expression in the BP lesional skin was detected by immunohistochemical staining. Infiltration of DCs, marked by DC-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…The pathophysiology of BP is still unclear, but autoantibodies to structured proteins in the dermal-epidermal junction and Th2 immunity are likely involved in this disorder ( 81 , 82 ). Multiple studies have identified a markedly increased concentration of TSLP in skin lesions, blister fluid, and sera of patients with BP, especially in the lower layer of the epidermis ( 83 86 ). Furthermore, the levels of TSLP in serum correlated with those in blisters ( 86 ).…”
Section: Tslp and Cutaneous Immune-mediated Disordersmentioning
confidence: 99%
See 3 more Smart Citations
“…The pathophysiology of BP is still unclear, but autoantibodies to structured proteins in the dermal-epidermal junction and Th2 immunity are likely involved in this disorder ( 81 , 82 ). Multiple studies have identified a markedly increased concentration of TSLP in skin lesions, blister fluid, and sera of patients with BP, especially in the lower layer of the epidermis ( 83 86 ). Furthermore, the levels of TSLP in serum correlated with those in blisters ( 86 ).…”
Section: Tslp and Cutaneous Immune-mediated Disordersmentioning
confidence: 99%
“…Multiple studies have identified a markedly increased concentration of TSLP in skin lesions, blister fluid, and sera of patients with BP, especially in the lower layer of the epidermis ( 83 86 ). Furthermore, the levels of TSLP in serum correlated with those in blisters ( 86 ). These findings imply that TSLP is involved in the immunopathogenesis of BP and could be released by keratinocytes in the epidermis of BP.…”
Section: Tslp and Cutaneous Immune-mediated Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…It was gradually revealed that TSLP is extensively involved in autoimmune diseases and cancers [ 3 ]. Moreover, expression of TSLP was found to participate in many inflammatory dermatoses, such as psoriasis vulgaris (PsV) [ 9 , 10 ], bullous pemphigoid (BP) [ 11 ], and alopecia areata [ 12 ]. Those diseases distinctly differ in clinical manifestations, pathology, and immune response patterns.…”
Section: Introductionmentioning
confidence: 99%